Nouvel atlas des champignons Tome I - Romagnesi, Henri (Bordas, 1970)
PROTOSTELIOMYCETES PROTOSTELIALES Ceratiomyxaceae Ceratiomyxa MYXOMYCETES LICEALES Cribrariaceae Cribrarla Lindbladia Dictydiacthaliaceae Dictydiacthalium Reticulariaccae Tubulifera Reticularia Lycogala Liccaceae Licca Listercllaccae Listerella echinosteliaies Echinosteliaccae Echinoslelium Clastodermataccae Clastodemia Barbcyclla TRICHIALES Diancmataccae Dianema Calomyxa Minakatellaccae • Minakatella Arcyriaceae * Arcyriatella Perichacna Arcyria Arcyodes Trichiaceae Metatrichia Protolrichia Hernitrichia Trichia Oligonema Caloncina Comuvia PHYSARALES Physaraccae Kelleromyxa • Protophysarum Fuligo Willkommlangea Lcocarpus Physarclla Badhamiopsis Badhamia Cratcrium Physarum Erionema Didymiaccae • Trabrooksia Diachca Physarina Didenna Mucilago Didymium Lepidodemia steaamonitaies Stemonitidaccae Elacomyxa Brefeldia Amaurochaete Symphytocarpus Collodemia • Leploderma Diacheopsis Paradiachca Macbridcola Paradiachcopsis Lamproderma Meriderma Enerhenema Comatricha Stemonaria Stemonitopsis Stemonitis